Mathematical Models for Contraceptive Use : A Review - lely kurnia; Nor Azah Samat (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2026)
This study reviews the development of quantitative approaches used to analyse contraceptive use, with a particular emphasis on mathematical and statistical modelling studies published between 2019 and April 2024. A systematic literature review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, combined with bibliometric analysis. Articles were retrieved from the Scopus and ScienceDirect databases using combinations of keywords related to contraceptive use and modelling approaches. The initial search identified 2,494 articles, which were filtered based on publication year, document type, language, and relevance to the research topic. After screening titles, abstracts, and applying inclusion and exclusion criteria, 62 articles were selected for final analysis. Bibliometric analysis using VOSviewer was conducted to identify keyword co-occurrence and co-authorship networks among researchers. The results indicate that research on contraceptive use has increased steadily during the study period and that various quantitative modelling approaches have been applied to analyse contraceptive dynamics across different countries. Quantitative approaches used in the reviewed studies include logistic regression, multilevel models, spatial analysis, Bayesian methods, time-series models, machine learning, artificial neural networks, and several mathematical population models. These approaches are widely used to examine determinants of contraceptive use, including socio-demographic and spatial factors influencing contraceptive adoption. Bibliometric analysis using VOSviewer identified six keyword clusters with 3,636 links and four author collaboration clusters with 66 links, indicating strong thematic relationships and growing research collaboration in this field. Overall, the findings highlight the increasing role of quantitative modeling approaches in understanding contraceptive dynamics and identifying factors influencing contraceptive use.